N‐3 polyunsaturated fatty acids worsen inflammation and fibrosis in experimental nonalcoholic steatohepatitis. (15th March 2014) - Provenzano, Angela; Milani, Stefano; Vizzutti, Francesco; Delogu, Wanda; Navari, Nadia; Novo, Erica; Maggiora, Marina; Maurino, Valter; Laffi, Giacomo; Parola, Maurizio; Marra, Fabio
Abstract Background & Aims n‐3 polyunsaturated fatty acids (PUFA) ameliorate fatty liver in experimental models, but their effects on inflammation and fibrosis during steatohepatitis are either controversial or lacking. We compared the effects of supplementation with olive oil (OO) alone or OO and n‐3 PUFA on the development and progression of experimental steatohepatitis. Methods Balb/C mice (≥5 mice/group) were fed a methionine‐ and choline‐deficient (MCD) diet or a control diet for 4 or 8 weeks. At the same time, mice were supplemented with n‐3 PUFA (eicosapentaenoic and docosahexahenoic acid, 25 mg together with 75 mg OO), or OO alone (100 mg), two times a week by intragastric gavage. Results After 8 weeks, mice on MCD/n‐3 had higher ALT levels compared to MCD/OO and more severe scores of inflammation, including a significant increase in the number of lipogranulomas (26.4 ± 8.4 vs. 5.1 ± 5 per field, P < 0.001). Intrahepatic expression of TNF‐α and CCL2 was higher in MCD/n‐3 mice at both time points. In addition, increased expression of the profibrogenic genes TIMP‐1 and TGF‐β, and more severe histological scores of fibrosis were evident in MCD/n‐3 mice. After 8 week of MCD diet, portal pressure was higher in mice receiving n‐3 than in those on OO alone (5.1 ± 1.4 vs. 7.0 ± 0.9 mmHg, P < 0.05). Analysis of hepatic fatty acid profile showed that supplementation resulted in effective incorporation of n‐3 PUFA. Conclusions In a murine model of steatohepatitis, supplementation with n‐3 PUFA and OO is associated with more severe necro‐inflammation and fibrosis than in mice treated with OO only.